Exploring Students Experience in Using AI to Improve Their Writing Skills - Tara Farihal; Zuhri Efendi (PT PUSTAKA CENDEKIA GROUP, 2026)
Artificial Intelligence (AI) has become an important tool in supporting students' academic writing. This study aimed to explore students' experience of using AI to improve their writing skills. A qualitative approach was employed through semi-structured interviews with 20 students of STKIP Muhammadiyah Aceh Barat Daya. The data were analyzed using thematic analysis with NVivo 12 software. The findings identified four main themes and seven sub-themes covering students' use of AI, feelings toward AI, perceived advantages, and challenges. Students perceived AI as a helpful tool for generating ideas, improving grammar, and increasing writing efficiency. However, concerns regarding academic honesty, limited access, contextual language, inaccurate information, and generic arguments were also reported. The study concluded that AI could effectively support academic writing when it was used critically, ethically, and responsibly.